[PP.09.12] PREVALENCE OF MASKED AND TRUE HYPERTENSION IN MILDLY DISEASED CHRONIC KIDNEY DISEASE. (September 2016) - Antza, C.; Papakatsika, S.; Natsis, M.; Stabouli, S.; Kotsis, V.
Abstract : Objective: The aim of this study was to indentify the prevalence of white coat (WCH) and masked hypertension (MH) in mildly diseased chronic kidney disease (CKD) patients(e-GFR:60–90) in comparison to normal kidney function (NKF) subjects (e-GFR >90). Figure. No caption available. Design and method: 558 consecutive subjects (48.5% male) with age 49.2 ± 19.8 years were included in the study. Subjects were never treated before for hypertension. Clinic BP measured three times in each subject using a mercury sphygmomanometer. All the subjects underwent 24h-ABPM on a usual working day. Patients with both ambulatory and clinic BP values in the hypertensive or normotensive range were defined as true hypertensives and normotensives respectively. WCH was defined as office hypertension with ambulatory normotension and MH as ambulatory hypertension with office normotension. e-GFR was estimated with MDRD equation. Results: Age and average 24SBP was significant higher in CKD patients (P < 0.0001) with no differences in clinic BP and average 24 h DBP compared to NKF subjects. Prevalence of true normotension and hypertension are shown in figure. In nominal regression analysis the four groups of hypertension status were included as dependent variable, factors the stage of kidney disease and the gender (reference category: true normotension). WCH, MH and true hypertension were significantly associated with mildly reduced stage of CKD (B = -0.75, P < 0.01, B = -1.24, P < 0.001, . B = -1.14, P < 0.0001 respectively). Conclusions: 24 h ambulatory BP monitoring is important to identify the real BP status in patients with mildly diseased CKD. Mild reduction in GFR is associated with increase 24 h SBP levels in similar clinic BP values.